Battery Energy Storage System for Emergency Supply and Improved Reliability of Power Networks - Marcin Szott; Szymon Wermiński; Marcin Jarnut; Jacek Kaniewski; Grzegorz Benysek (Energies, 2021)
This paper introduces the concept of a battery energy storage system as an emergency power supply for a separated power network, with the possibility of island operation for a power substation with one-side supply. This system, with an appropriately sized energy storage capacity, allows improvement in the continuity of the power supply and increases the reliability of the separated network at a specified time during the limitation of power transmission as a result of damage or disconnection of the main power line. This paper presents and describes a specific method of energy storage system dimensioning based on real measurement data. Based on the obtained parameters, an analysis of the reliability improvement of the considered network was performed. The implementation of the battery energy storage system will contribute to a more than 5-fold reduction in the occurrence of power outages in the time interval from 3 min to 1.5 h, which will clearly reduce the System Average Interruption Frequency Index and System Average Interruption Duration Index factors. In this paper, the network conditions for operational normality and failure are presented and the cost for implementation of an energy storage system (about EUR 1 million) is compared with the possible implementation of an additional power line (about EUR 5 million) to a specific power substation.